Manifestasi Hak Asasi Mantan Narapidana dalam Pengisian Jabatan Negara Menurut Undang-Undang Nomor 7 Tahun 2017 tentang Pemilihan Umum - Muhammad Ansor Lubis; Faisal Akbar Nasution; Mirza Nasution; Muhammad Yamin (ARBITER: Jurnal Ilmiah Magister Hukum, 2023)
In accordance with one of the ideals of the General Election, namely to produce quality representatives of the people and the spirit to create a government free from corruption, collusion and nepotism. In the 2019 legislative election, the KPU established KPU regulation No. 20 of 2018 concerning the Nomination of Members of the DPR, Provincial DPRD, and Regency/City DPRD in the 2019 Election. The KPU added a requirement to become a member of the legislature which in article 4 paragraph (3) states that for former convicts of drug dealers, sexual crimes against children, or corruption prohibited from participating in the nomination of members of the legislature. These provisions are considered contrary to Law no. 7 of 2017 concerning General Elections. The formulation of the problem in this paper is how to manifest the fulfillment of prisoners' human rights in filling state positions as regulated in Law Number 7 of 2017 concerning General Elections. The research method used is a normative juridical research method. Normative research requires a statutory approach and a conceptual approach. The data collection technique used is through the study of documents and literature on secondary data in the form of primary, secondary and tertiary legal materials. The conclusion is that there are several decisions of the Constitutional Court, the Supreme Court and the Decisions of the Bawaslu which also hinder the enactment of these provisions. These provisions relate to the limitation of Human Rights, namely the limitation of Political Rights, namely the right to be elected as regulated in Law Number 39 of 1999 concerning Human Rights.